Formula used:

The factors of a polynomial can be find by taking a common factor and this method is called factor by grouping,

\(ab+ac+bd+cd=a(b+c)+d(b+c)\)

\(=(a+d)(b+c)\)

Or,

\(ab-ac+bd-cd=a(b—c)+d(b-c)\)

\(=(a+d)(b-c)\)

Calculation:

Consider the polynomial \(2x^{3}-8x^{2}-9x+36\).

This is a four term polynomial, factorization of this polynomial can be find by factor by grouping as,

\(2x^{3}-8x^{2}-9x+36=(2x^{3}-8x^{2})-(9x-36)\)

\(=2x^{2}(x-4)-9(x-4)\)

As, \((x-4)\) is the common factor of the polynomial,

The polynomial can be factorized as,

\(2x^{2}(x-4)-9(x-4)=(x-4)(2x^{2}-9)\)

Therefore, the factorization of the polynomial \(2x^{3}-8x^{2}-9x+36\) is \((x-4)(2x^{2}-9)\).

The factors of a polynomial can be find by taking a common factor and this method is called factor by grouping,

\(ab+ac+bd+cd=a(b+c)+d(b+c)\)

\(=(a+d)(b+c)\)

Or,

\(ab-ac+bd-cd=a(b—c)+d(b-c)\)

\(=(a+d)(b-c)\)

Calculation:

Consider the polynomial \(2x^{3}-8x^{2}-9x+36\).

This is a four term polynomial, factorization of this polynomial can be find by factor by grouping as,

\(2x^{3}-8x^{2}-9x+36=(2x^{3}-8x^{2})-(9x-36)\)

\(=2x^{2}(x-4)-9(x-4)\)

As, \((x-4)\) is the common factor of the polynomial,

The polynomial can be factorized as,

\(2x^{2}(x-4)-9(x-4)=(x-4)(2x^{2}-9)\)

Therefore, the factorization of the polynomial \(2x^{3}-8x^{2}-9x+36\) is \((x-4)(2x^{2}-9)\).